2012
DOI: 10.4049/jimmunol.1200599
|View full text |Cite
|
Sign up to set email alerts
|

Differential Idiotype Utilization for the In Vivo Type 14 Capsular Polysaccharide-Specific Ig Responses to Intact Streptococcus pneumoniae versus a Pneumococcal Conjugate Vaccine

Abstract: Murine IgG responses specific for the capsular polysaccharide (pneumococcal capsular polysaccharide serotype 14; PPS14) of Streptococcus pneumoniae type 14 (Pn14), induced in response to intact Pn14 or a PPS14–protein conjugate, are both dependent on CD4+ T cell help but appear to use marginal zone versus follicular B cells, respectively. In this study, we identify an idiotype (44.1-Id) that dominates the PPS14-specific IgG, but not IgM, responses to intact Pn14, isolated PPS14, and Group B Streptococcus (stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 77 publications
(97 reference statements)
2
31
0
Order By: Relevance
“…This is consistent with the augmented MCPS-specific IgG response observed in MenC-primed mice following booster immunization with isolated MCPS, also a TI Ag, or a soluble covalent conjugate of MCPS and TT. Results similar to that obtained with MenC are also observed using another GN bacteria, A. baumannii expressing PNAG, that is, a primary PNAG-specific IgG response that peaks relatively late (by day [14][15][16][17][18][19][20][21] and that is independent of CD4 + T cells, and an augmented PNAG-specific IgG response following booster immunization with A. baumannii that requires CD4 + T cells during the primary, but not during the booster immunization. These data further support the notion that the regulation of capsular PSspecific IgG responses to intact bacteria is dependent on the nature of the subcapsular domain, and suggest a potential, general dichotomy between GP and GN bacteria.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is consistent with the augmented MCPS-specific IgG response observed in MenC-primed mice following booster immunization with isolated MCPS, also a TI Ag, or a soluble covalent conjugate of MCPS and TT. Results similar to that obtained with MenC are also observed using another GN bacteria, A. baumannii expressing PNAG, that is, a primary PNAG-specific IgG response that peaks relatively late (by day [14][15][16][17][18][19][20][21] and that is independent of CD4 + T cells, and an augmented PNAG-specific IgG response following booster immunization with A. baumannii that requires CD4 + T cells during the primary, but not during the booster immunization. These data further support the notion that the regulation of capsular PSspecific IgG responses to intact bacteria is dependent on the nature of the subcapsular domain, and suggest a potential, general dichotomy between GP and GN bacteria.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies using intact heat-killed S. pneumoniae and a soluble pneumococcal conjugate vaccine strongly suggested that PS-specific IgG responses were derived from marginal zone and follicular B cells, respectively (18,19), with elicitation of distinct idiotypes on the PS-specific (serotype 14) IgG (17). Indeed, mice primed with intact serotype 14 S. pneumoniae do not elicit an augmented PS-specific IgG response following booster immunization with a soluble type 14 pneumococcal conjugate vaccine, in which the carrier protein is pneumococcal surface protein A (33), but do elicit an augmented response following booster immunization with intact GBS-III expressing type 14 PS (21).…”
Section: Mice Primed With Either Menc or A Soluble Conjugate Of Mcps-mentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated previously that polysaccharide (PS)-and protein-specific IgG responses to intact extracellular bacteria (20), as well as soluble conjugate vaccines (21), are dependent on CD4 + T cells. However, the PS-specific IgG response to an intact bacterium arose from MZ B cells expressing a distinct and dominant idiotype, in contrast to the same PS-specific IgG response to a soluble conjugate vaccine, which arose from follicular B cells expressing a different idiotype(s) (21)(22)(23). This dichotomy was specifically dependent on whether the PS was coexpressed with protein in a particulate or soluble form (24).…”
Section: Endritic Cells (Dc) Monocytes (And Monocyte-derived Cellsmentioning
confidence: 91%
“…In this regard, we demonstrated previously that anti-PPS14 IgG elicited in response to a covalent conjugate of PPS14 and protein presented on the surface of 1-mm latex particles exhibits a distinct idiotype (44.1-Id) (23,24) that is secreted by MZ B cells (21,22), whereas the soluble conjugate fails to elicit 44.1-Id and instead induces an anti-PPS14 IgG response from follicular B cells. The potential relationship between these latter observations and the use of distinct APCs to induce CD4 + T cell activation in response to these different forms of Ag remains to be determined.…”
Section: Discussionmentioning
confidence: 99%